Evaluation of Gulf Coast Ticks (Acari: Ixodidae) for Ehrlichia and Anaplasma Species. Issue 2 (28th December 2016) - Allerdice, Michelle E. J.; Hecht, Joy A.; Karpathy, Sandor E.; Paddock, Christopher D.
Abstract : Amblyomma maculatum Koch (the Gulf Coast tick) is an aggressive, human-biting ixodid tick distributed throughout much of the southeastern United States and is the primary vector for Rickettsia parkeri, an emerging human pathogen. Amblyomma maculatum has diverse host preferences that include white-tailed deer, a known reservoir for Ehrlichia and Anaplasma species, including the human pathogens E. ewingii and E. chaffeensis . To examine more closely the potential role of A. maculatum in the maintenance of various pathogenic Ehrlichia and Anaplasma species, we screened DNA samples from 493 questing adult A. maculatum collected from six U.S. states using broad-range Anaplasmataceae and Ehrlichia genus-specific PCR assays. Of the samples tested, four (0.8%) were positive for DNA of Ehrlichia ewingii, one (0.2%) was positive for Anaplasma platys, and one (0.2%) was positive for a previously unreported Ehrlichia species closely related to Ehrlichia muris and an uncultivated Ehrlichia species from Haemaphysalis longicornis ticks in Japan. No ticks contained DNA of Ehrlichia chaffeensis, Ehrlichia canis, the Panola Mountain Ehrlichia, or Anaplasma phagocytophilum . This is the first identification of E. ewingii, A. platys, and the novel Ehrlichia in questing Gulf Coast ticks; nonetheless the low prevalence of these agents suggests that A. maculatum is not likely an important vector of these zoonotic pathogens.